2005
DOI: 10.1097/01.mlr.0000170405.66264.23
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in the Mental Health Problems and Use of Mental Health Care

Abstract: Overall, our study shows wide variation in mental health morbidity and use of mental health care across racial and ethnic groups in the United States. These results can help to focus efforts aimed at understanding the underlying causes of the differences we observe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 31 publications
10
122
2
Order By: Relevance
“…The articles present findings from the seven epidemiological studies: the ECA Wells, Hough, Golding, Burnam, & Karno, 1987;Wells, Hough, Golding, Burnam, & Karno, 1989), NCS , MAPSS (Peifer, Hu, & Vega, 2000;Vega, Kolody, & Aguilar-Gaxiola, 2001;Vega et al, 1999), the Puerto Rico Mental Health Utilization Study (PRMHUS; AlbizuGarcia, Alegría, Freeman, & Vera, 2001;Alegría et al, 1991;Pescosolido, Wright, Alegría, & Vera, 1998;Vera, Alegría, Freeman, Robles, Pescosolido, & Pena, 1998), South Florida Refugee Study (Portes et al, 1992), National Surveys on Drug Use and Health (NSDUH; Harris et al, 2005), and the Robert Wood Johnson Foundation's Healthcare for Communities Study (RWJF HCS; Wells et al, 2001;Young, Klap, Sherbourne, & Wells, 2001). The 16 publications are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles present findings from the seven epidemiological studies: the ECA Wells, Hough, Golding, Burnam, & Karno, 1987;Wells, Hough, Golding, Burnam, & Karno, 1989), NCS , MAPSS (Peifer, Hu, & Vega, 2000;Vega, Kolody, & Aguilar-Gaxiola, 2001;Vega et al, 1999), the Puerto Rico Mental Health Utilization Study (PRMHUS; AlbizuGarcia, Alegría, Freeman, & Vera, 2001;Alegría et al, 1991;Pescosolido, Wright, Alegría, & Vera, 1998;Vera, Alegría, Freeman, Robles, Pescosolido, & Pena, 1998), South Florida Refugee Study (Portes et al, 1992), National Surveys on Drug Use and Health (NSDUH; Harris et al, 2005), and the Robert Wood Johnson Foundation's Healthcare for Communities Study (RWJF HCS; Wells et al, 2001;Young, Klap, Sherbourne, & Wells, 2001). The 16 publications are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven Harris et al, 2005;Hough et al, 1987;Portes et al, 1992;Wells et al, 1987;Wells et al, 2001;Young et al, 2001) articles compared service use rates of Latinos with other racial and/or ethnic groups. For instance, Alegría et al (2002) used NCS data to compare the use of outpatient mental health services between Latinos (i.e., Mexican Americans, Cubans, Puerto Ricans and other Latinos), non-Latino Whites, and African Americans in a national representative sample of the non-institutionalized U.S. population.…”
Section: Study Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found that Hispanic children were at higher risk for positive modifiers, although previous studies have found Hispanic individuals as a group to underreport BH symptoms compared with other ethnic groups. 22,34,35 One previous study even suggested that a lower cutpoint on the PSC would be needed to identify Mexican American children. 35 Although other studies report a relationship between race/ethnicity and positive scores on the PSC, 15,34,36 there has been no attempt to separate the impact of socioeconomic status.…”
Section: Figurementioning
confidence: 99%
“…22,34,35 One previous study even suggested that a lower cutpoint on the PSC would be needed to identify Mexican American children. 35 Although other studies report a relationship between race/ethnicity and positive scores on the PSC, 15,34,36 there has been no attempt to separate the impact of socioeconomic status. In this study of children insured by Medicaid (ie, controlling for socioeconomic status), race/ethnicity predicted positive modifiers, and minority children were more likely to be among those newly identified by BH screens.…”
Section: Figurementioning
confidence: 99%